Medical resin composition containing hexafluoroisopropanol group
Patent Information
- Application Number
- JP2022055624
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-26
- Filing Date
- 2022-03-30
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Fluororesins used in medical materials exhibit excessively high water repellency, leading to a decrease in cell non-adhesiveness over time, which is a concern for applications requiring biocompatibility and mechanical properties.
A medical resin composition containing a hexafluoroisopropanol group (HFIP) is developed, which maintains a moderate water droplet contact angle while avoiding excessively high water repellency, incorporating components such as epoxy resins, phenolic resins, and polysiloxanes with specific atomic group structures.
The composition achieves an appropriate water droplet contact angle, enhancing biocompatibility and antithrombotic properties while suppressing biofouling, suitable for medical applications.
Smart Images

Figure 2022159148000001 
Figure 2022159148000002 
Figure 2022159148000003
Abstract
Description
[Technical Field]
[0001] One embodiment of the present invention relates to a medical resin composition containing a hexafluoroisopropanol group. [Background technology]
[0002] In the development of medical materials essential for advanced medicine and bio-research, such as diagnostics, drug discovery, and regenerative medicine, components that come into contact with cells and living organisms require control over cell adhesion, antithrombotic properties, and biocompatibility. Polymers are applied to medical materials, utilizing the biocompatibility of phosphatidylcholine groups, glucoside groups, and amino acid residues.
[0003] On the other hand, medical materials such as artificial organs and cell transplant sheets require excellent mechanical properties, and polymer materials such as polyethylene, polypropylene, polyvinyl chloride, nylon, polyurethane, polylactic acid, polyglycolic acid, poly(meth)acrylic acid, poly(meth)acrylic acid derivatives, poly(meth)acrylamide, poly(meth)acrylamide derivatives, polysulfone, cellulose, cellulose derivatives, silicone, and polydimethylsiloxane (hereinafter sometimes referred to as PDMS) are used.
[0004] PDMS is inexpensive, easy to mold, and low in toxicity, making it suitable for use in medical components such as microfluidics. However, it is known to be highly hydrophobic and can cause biofouling, and Non-Patent Literature 1 reports on the study of various hydrophilization treatments.
[0005] Highly hydrophobic polymers also require suppression of biofouling. One method for suppressing biofouling is hydrophilization treatment of polymers. Known hydrophilization treatments include plasma surface treatment and chemical treatment using chemicals. The former, plasma surface treatment, has limitations, such as the loss of hydrophilicity in a short period of time, and the latter, chemical treatment, has limitations, such as the need for chemicals to have adverse effects on living organisms.
[0006] On the other hand, Patent Document 1 reports that fluororesins have excellent non-adhesion properties to cells due to their high water repellency, low surface free energy and low intermolecular cohesive force, as well as excellent chemical resistance, and have been used as biochips. [Prior art documents] [Non-patent literature]
[0007] [Non-Patent Document 1] Hongbin Zhang, Mu Chiao, “Anti-fouling Coatings of Poly(dimethylsiloxane) Devices for Biological and Biomedical Applications”, J. Med. Biol. Eng., 35: 143-155 (2015) [Patent Documents]
[0008] [Patent Document 1] Japanese Patent Publication No. 2019-128149 [Overview of the Initiative] [Problems that the invention aims to solve]
[0009] As shown in Patent Document 1, fluororesins can be expected to provide non-adhesion to cells. On the other hand, these fluororesins are highly hydrophobic due to their high water repellency, and there are concerns that continuous use may lead to a decrease in cell non-adhesion. Taking the above into consideration, the present invention provides a medical resin composition that can utilize low intermolecular cohesive forces due to low surface free energy based on fluorine, while avoiding excessively high water repellency. [Means for solving the problem]
[0010] In order to achieve the above object, the present inventors conducted extensive studies. As a result, it was found that a medical resin composition containing a hexafluoroisopropanol group (hereinafter sometimes referred to as a HFIP group) represented by the general formula (1) can provide a medical resin composition having an appropriate water droplet contact angle while avoiding excessive water repellency.
[0011] The present invention is as follows.
[0012] 1. A medical resin composition comprising the following component (A) and the following component (B). (A): A resin containing an atomic group represented by the following formula (1) (B): A solvent
Chemical formula
Chemical formula
Chemical formula
Chemical formula
[0013] According to the present invention, a medical resin composition containing a hexafluoroisopropanol group is provided.
[0014] According to one embodiment of the present invention, a medical resin composition is provided that has an appropriate water droplet contact angle while avoiding excessively high water repellency. [Modes for carrying out the invention]
[0015] The embodiments of the present invention will be described in detail below. However, the embodiments of the present invention are not limited to the embodiments and examples described below. In this specification, the notation "X~Y" in numerical range descriptions shall mean "X or greater than or equal to Y" unless otherwise specified. In this specification, when a group (atomic group) is not specified as substituted or unsubstituted, it includes both unsubstituted and substituted groups. For example, "alkyl group" includes not only unsubstituted alkyl groups but also substituted alkyl groups. In this specification, "polysiloxane" refers to a polymer compound containing siloxane bonds. In this specification, "biocompatibility" means the property of having affinity with living tissues and organs and being less likely to cause foreign body reactions or rejection reactions.
[0016] Detailed embodiments of the present invention will be described in the following order. 1. Medical resin compositions 2. Medical component using a medical resin composition, and method for forming the component.
[0017] 1. Medical resin compositions The medical resin composition of the present invention is (A) Component: A resin containing an atomic group represented by the following formula (1). (B) Component: Solvent [ka] (In equation (1) above, the dashed line represents a bond with another atomic group.) It is characterized by including.
[0018] [(A) component] Component (A) is a resin containing an atomic group represented by the following formula (1) at the side chains and / or ends of the main chain of the resin. [ka] (In equation (1) above, the dashed line represents a bond with another atomic group.)
[0019] The resin is preferably one or more selected from the group consisting of epoxy resins, phenolic resins, novolac resins, polysiloxanes, polyimides, polyamides, polyesters, and polyethers.
[0020] Of these, it is preferable that the resin contains one or more selected from the group consisting of a structure containing silicon represented by the following formula (1-1) and formula (1-2), a structure containing nitrogen represented by formula (1-3) and a group represented by Ar1, a structure containing oxygen represented by formula (1-4) and a group represented by Ar2, a structure containing novolac represented by formula (1-5), and a structure containing silicon represented by formula (1-6) and a group represented by Ar3. [ka] (In equation (1-1) above, the dashed line represents a bond with another atomic group.) [ka] (In equation (1-2) above, the dashed line represents a bond with another atomic group.)
[0021] The silicon-containing resins represented by formulas (1-1) and (1-2) are synthesized by methods that are not particularly limited, but for example, they can be synthesized by first obtaining a polymerizable monomer through a hydrosilylation reaction between a silicon compound containing a structure represented by Si-H and CH2=CH-CH-C(CF3)2-OH, and then polymerizing the polymerizable monomer as previously reported (FR2815354, Materials Letters 237 (2019) 282-285).
[0022] [ka] In formulas (1-3), Ar1 is a group containing an aromatic hydrocarbon group having 6 to 24 carbon atoms, and some or all of the hydrogen atoms of the aromatic hydrocarbon group may be substituted with an alkyl group having 1 to 3 carbon atoms, and may include structures represented by -CH2-, -CO-, -SO2-, -C(CH3)2-, -C(CF3)2-, ma represents an integer from 1 to 3, and na represents an integer from 1 to 4. In formulas (1-3), the dashed line represents a bond with another atomic group.
[0023] Examples of aromatic hydrocarbon groups having 6 to 24 carbon atoms include groups containing benzene rings, naphthalene rings, and anthracene rings. The aforementioned aromatic rings, such as benzene rings, naphthalene rings, and anthracene rings, may be included individually or as two or more aromatic rings linked together. An example of a structure in which two or more aromatic rings are linked together is a biphenyl structure. Examples of alkyl groups having 1 to 3 carbon atoms include methyl groups, ethyl groups, n-propyl groups, and isopropyl groups. Ar1 may include structures represented by -CH2-, -CO-, -SO2-, -C(CH3)2-, and -C(CF3)2-, for example, a structure in which benzene rings are linked by -CH2- can be exemplified.
[0024] [ka] In formulas (1-4), Ar2 is a group containing an aromatic hydrocarbon group having 6 to 24 carbon atoms, and some or all of the hydrogen atoms of the aromatic hydrocarbon group may be substituted with an alkyl group having 1 to 3 carbon atoms, and may include structures represented by -CH2-, -CO-, -SO2-, -C(CH3)2-, -C(CF3)2-, mb represents an integer from 1 to 3, and nb represents an integer from 1 to 4. In formulas (1-4), the dashed line represents a bond with another atomic group.
[0025] Examples of aromatic hydrocarbon groups having 6 to 24 carbon atoms include groups containing benzene rings, naphthalene rings, and anthracene rings. The aforementioned aromatic rings, such as benzene rings, naphthalene rings, and anthracene rings, may be included individually or as two or more aromatic rings linked together. An example of a structure in which two or more aromatic rings are linked together is a biphenyl structure. Examples of alkyl groups having 1 to 3 carbon atoms include methyl groups, ethyl groups, n-propyl groups, and isopropyl groups. Ar2 may include structures represented by -CH2-, -CO-, -SO2-, -C(CH3)2-, and -C(CF3)2-, for example, a structure in which benzene rings are linked by -CH2- can be exemplified.
[0026] [ka] (In the above formulas (1-5), R 1 R is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. 2 R is a group containing a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or an aromatic hydrocarbon having 6 to 24 carbon atoms. 3 (where is an alkyl group with 1 to 4 carbon atoms, t is an integer from 1 to 2, p is an integer from 0 to 2, nc is an integer from 1 to 3, and the wavy line represents a bond with another atomic group.) The resin containing the structure represented by formula (1-5) is synthesized by a method that is not particularly limited, but is synthesized with reference to the method described in a previous publication (Japanese Patent Application Publication No. 2014-141655).
[0027] [ka] In formulas (1-6), Ar3 is a group containing an aromatic hydrocarbon group having 6 to 24 carbon atoms, and some or all of the hydrogen atoms of the aromatic hydrocarbon group may be substituted with an alkyl group having 1 to 3 carbon atoms, and may include structures represented by -CH2-, -CO-, -SO2-, -C(CH3)2-, -C(CF3)2-, md represents an integer from 1 to 3, and nd represents an integer from 1 to 4. In formulas (1-6), the dashed line represents a bond with another atomic group.
[0028] Examples of aromatic hydrocarbon groups having 6 to 24 carbon atoms include groups containing benzene rings, naphthalene rings, and anthracene rings. The aforementioned aromatic rings, such as benzene rings, naphthalene rings, and anthracene rings, may be included individually or as two or more aromatic rings linked together. An example of a structure in which two or more aromatic rings are linked together is a biphenyl structure. Examples of alkyl groups having 1 to 3 carbon atoms include methyl groups, ethyl groups, n-propyl groups, and isopropyl groups. Ar3 may include structures represented by -CH2-, -CO-, -SO2-, -C(CH3)2-, and -C(CF3)2-, for example, a structure in which benzene rings are linked by -CH2- can be exemplified.
[0029] The structure represented by formula (1-3) is preferably one or more structures selected from the group consisting of formulas (1-3a) to (1-3f) below. The resin containing the said structure is synthesized by methods described in the previously published Japanese Patent Publication Nos. 2007-119503, 2007-119504, 2008-150534, 2013-10096, 2014-125455, 2014-128787, 2014-128788, 2014-129339, 2014-129340, and 2016-137484, with reference to the methods described in the previously published Japanese Patent Publication Nos. 2007-119503, 2007-119504, 2008-150534, 2013-10096, 2014-125455, 2014-128787, 2014-128788, 2014-129339, 2014-129340, and 2016-137484. [ka] (In equation (1-3a) above, the dashed line represents a bond with another atomic group.) [ka] (In equation (1-3b) above, the dashed line represents a bond with another atomic group.) [ka] (In equation (1-3c) above, the dashed line represents a bond with another atomic group.) [ka] (In equation (1-3d) above, the dashed line represents a bond with another atomic group.) [ka] (In equation (1-3e) above, the dashed line represents a bond with another atomic group.) [ka] (In equation (1-3f) above, the dashed line represents a bond with another atomic group.)
[0030] The structure represented by formula (1-4) is preferably one or more structures selected from the group consisting of formulas (1-4a) to (1-4c) below. The resin containing this structure is synthesized by any method, although the method described in previously published reports (WO2012 / 165435), (WO2012 / 165436), and (WO2014 / 34541) is not particularly limited. [ka] (In equation (1-4a) above, the wavy line represents a bond with another atomic group.) [ka] (In equation (1-4b) above, the dashed line represents a bond with another atomic group.)
[0031] [ka] In equation (1-4c) above, n represents an integer between 1 and 3, and the dashed line represents a bond with another atomic group. The resin containing the structure represented by formula (1-4c) is synthesized by a method that is not particularly limited, but based on previously reported (JP 2010-235501) and (JP 2007-45820), 2-(4-hydroxyphenyl)hexafluoropropan-2-ol, 3,5-bis(1,1,1,3,3,3-hexafluoro-2-hydroxyisopropyl)phenol, etc. are synthesized, and then converted into a polymerizable derivative by introducing an acrylic group or a methacrylic group into the compound, and finally polymerizing the resulting polymerizable compound. Known methods can be used to introduce the acrylic group or methacrylic group.
[0032] The structure represented by formula (1-6) is preferably the structure represented by formula (1-6a) below. The resin containing this structure is synthesized by a method that is not particularly limited, but is synthesized with reference to the method described in a previous report (WO2019 / 167770). [ka] (In equation (1-6a) above, the wavy line represents a bond with another atomic group.)
[0033] The resin containing the atomic group represented by formula (1) above can be used alone or in combination of two or more types.
[0034] The aforementioned component (A) may further contain polymerizable sites. Examples of polymerizable sites include epoxy groups, oxetane groups, acryloyl groups, and methacryloyl groups. These groups are presumed to contribute to the curing of the resin composition described later by polymerization within the resin.
[0035] The weight-average molecular weight (Mw) of the resin containing the atomic group represented by formula (1), which is component (A), is preferably 800 to 500,000, and particularly preferably 1,000 to 200,000, from the viewpoint of improving the durability and mechanical strength of medical components processed into films, tubes, and other molded articles, as well as from the viewpoint of processability. If the weight-average molecular weight (Mw) of the resin containing the atomic group represented by formula (1) is above the lower limit, it exhibits excellent durability and mechanical strength. If the weight-average molecular weight (Mw) of the resin containing the atomic group represented by formula (1) is below the upper limit, it exhibits excellent processability. In this specification, the weight-average molecular weight (Mw) refers to the value obtained by creating a calibration curve using polystyrene as a standard substance and calculating the measurement value by gel permeation chromatography under the following conditions. Equipment: Manufactured by Tosoh Corporation, Product name: HLC-8320GPC Column: Manufactured by Tosoh Corporation, Product name: TSK gel GMH XL Connect three of them in series. Eluent: Tetrahydrofuran
[0036] Medical components obtained using the resin composition of this embodiment have an appropriate water droplet contact angle while avoiding excessively high water repellency. This is presumed to be due to the atomic group represented by formula (1) in the resin. It is presumed that the presence of the atomic group represented by formula (1) in the resin allows for an appropriate water droplet contact angle while suppressing water repellency compared to resins that do not contain this atomic group.
[0037] [(B) Component] Component (B) is a solvent. As the solvent, water or any organic solvent can be used, as long as it can dissolve or disperse component (A). Specifically, examples include water, alcohols, ketones, aromatic hydrocarbon compounds, aliphatic hydrocarbon compounds, ethers, esters, amides, etc.
[0038] Preferred solvents include water, methanol, ethanol, isopropanol, 1,1,1-trifluoroethanol, 1,1,1,3,3,3-hexafluoroisopropanol (hereinafter sometimes referred to as HFIP), and other alcohols; acetone, methyl ethyl ketone, methyl isobutyl ketone, and other ketones; alkyl ethers such as diethyl ether, diisopropyl ether, and tetrahydrofuran; aromatic hydrocarbon compounds such as benzene, toluene, and xylene; aliphatic hydrocarbon compounds such as hexane, heptane, octane, and cyclohexane; propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, cyclohexanone, ethyl lactate, butyl acetate, γ-butyrolactone, diacetone alcohol, diglyme, methyl isobutyl ketone, 2-methoxy-1-methylethyl acetate, 3-methoxybutyl acetate, 2-heptanone, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.
[0039] Furthermore, glycols, glycol ethers, and glycol ether esters can also be used as solvents. Specifically, examples include Certol (registered trademark) manufactured by Daicel Corporation and HiSolve (registered trademark) manufactured by Toho Chemical Industry Co., Ltd. More specifically, cyclohexanol acetate, dipropylene glycol dimethyl ether, propylene glycol diacetate, dipropylene glycol methyl-n-propyl ether, dipropylene glycol methyl ether acetate, 1,4-butanediol diacetate, 1,3-butylene glycol diacetate, 1,6-hexanediol diacetate, 3-methoxybutyl acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, triacetin, 1,3-butyl Examples include ethylene glycol, propylene glycol-n-propyl ether, propylene glycol-n-butyl ether, dipropylene glycol methyl ether, dipropylene glycol ethyl ether, dipropylene glycol-n-propyl ether, dipropylene glycol-n-butyl ether, tripropylene glycol methyl ether, tripropylene glycol-n-butyl ether, triethylene glycol dimethyl ether, diethylene glycol butyl methyl ether, tripropylene glycol dimethyl ether, and triethylene glycol dimethyl ether.
[0040] The solvent may be a single solvent or a mixture of solvents.
[0041] The amount of solvent used is not particularly limited, but it is used so that the total solids content concentration (concentration of components other than volatile solvents) in the resin composition is usually 5 to 60% by mass, preferably 10 to 50% by mass. By appropriately adjusting the total solids content concentration, for example, when a film is formed as an example of molding, the ease of forming a thin film and the uniformity of the film thickness tend to improve.
[0042] When using the medical resin composition to form a resin film as described later, it is preferable to use a solvent that does not damage the substrate.
[0043] When using the medical resin composition to form a resin film as described later, it is preferable to use an appropriate solvent depending on the heat resistance of the substrate. By using a solvent with a boiling point lower than the thermal decomposition temperature, glass transition temperature, or melting point of the substrate, the impact on the substrate can be minimized when the solvent is removed by heating.
[0044] [Medical resin composition] The medical resin composition of the present invention comprises a resin containing the atomic group represented by formula (1), which is component (A), and a solvent, which is component (B). In other words, the medical resin composition of the present invention is obtained by dissolving or dispersing component (A) in the solvent, which is component (B).
[0045] [Other ingredients (third ingredient)] Other components (third components) may be included in the medical resin composition to the extent that they do not significantly impair the effects of the present invention. These other components (third components) are not particularly limited, but include resins containing one or more selected from the group consisting of phosphatidylcholine groups, glucoside groups, amino acid residues, alkylene oxide bonds such as ethylene oxide and propylene oxide, phosphate esters, phosphoric acid, sulfonic acid esters, sulfonic acid, carboxylic acid esters, carboxylic acids, and quaternary ammonium compounds, and resins obtained by polymerizing one or more polymerizable monomers selected from the group consisting of butyl (meth)acrylate, stearyl (meth)acrylate, N,N-dimethylacrylamide, N-vinylpyrrolidone, and hydroxyethyl (meth)acrylate (hereinafter, resins obtained by polymerizing polymerizable monomers may be referred to as polymers). These resins may also be used to adjust the biocompatibility and hydrophilicity of medical components obtained from the medical resin composition of the present invention.
[0046] Other components (third components) include resins such as polyethylene, polypropylene, polyvinyl chloride, nylon, polyurethane, polylactic acid, polyglycolic acid, poly(meth)acrylic acid, poly(meth)acrylic acid derivatives, poly(meth)acrylamide, poly(meth)acrylamide derivatives, polysulfone, cellulose, cellulose derivatives, silicone, and polydimethylsiloxane (hereinafter sometimes referred to as PDMS). These resins may also be used to adjust the mechanical strength of medical components obtained from the medical resin composition of the present invention.
[0047] The composition may also contain a crosslinking agent as a third component. Examples of crosslinking agents include those having a melamine structure, a urea structure, a polybasic acid structure, an isocyanate group, or an epoxy group. These crosslinking agents are thought to primarily react with the hydroxyl groups contained in component (A) to form a crosslinked structure. It is presumed that the formation of this crosslinked structure contributes to the curing of the resin composition.
[0048] Other components (third component) may include photopolymerization initiators or thermal polymerization initiators. These components are presumed to contribute to the curing of the resin composition described later by promoting the polymerization reaction of the polymerizable sites mentioned above.
[0049] The photopolymerization initiator or thermal polymerization initiator is preferably a photoradical polymerization initiator or a photocationic polymerization initiator, a thermal radical polymerization initiator, or a thermal cationic polymerization initiator. Photocationic polymerization initiators and thermal cationic polymerization initiators are preferred because they can promote the polymerization reaction when the polymerizable site is an epoxy group or an oxetane group. Photoradical polymerization initiators and thermal radical polymerization initiators are preferred because they can promote the polymerization reaction when the polymerizable site is an acryloyl group or a methacryloyl group.
[0050] The amount of the aforementioned other components used is not particularly limited, but when the total amount of the medical resin composition is 100% by mass, the amount of other components used is preferably 0.1% to 40% by mass. 1% to 30% by mass is particularly preferred.
[0051] 2. Medical component using a medical resin composition, and method for molding the component. The medical resin composition of the present invention may be used as a medical component by forming a resin film on a substrate by methods such as coating, spraying, or vapor deposition. Alternatively, it may be molded into desired shapes such as tubes, grooves, threads, nonwoven fabrics, porous structures, blocks, or lumps, such as microfluidic channels, to serve as a medical component.
[0052] The medical component obtained using the medical resin composition of the present invention preferably has a standard deviation of 2.9 or less of the contact angle when 2 μL of aqueous solutions (pH=7 is pure water) with pH values of 2, 4, 7, 9, and 10 at 25°C ± 2.0°C are dropped onto the component and the contact angle of the droplet is measured after 1 second. The smaller the aforementioned standard deviation, the smaller the change in the physical properties of the medical component is presumed to be. In particular, if the amount of change is small with respect to alkaline solutions, it can be presumed that the medical component has alkali resistance.
[0053] For cleaning medical components, especially those contaminated with organic matter, alkaline cleaning solutions or neutral cleaning solutions containing enzymes are often used. It is presumed that if medical components possess alkali resistance, changes in their physical properties will be reduced when they are cleaned with alkaline cleaning solutions. Therefore, from the perspective of continuous use of medical components and reducing the risk of contamination due to organic matter, it is considered desirable for medical components to possess alkali resistance.
[0054] From the viewpoint of alkali resistance as described above, component (A) of the medical resin composition of the present invention is preferably a resin containing one or more structures selected from those represented by formulas (1-1), (1-3), or (1-6), and is particularly preferably a resin containing one or more structures selected from those represented by formulas (1-1), (1-3a), or (1-6a).
[0055] The medical component obtained using the medical resin composition of the present invention is preferably 60° to 100°, and more preferably 65° to 95°C, when 2 μL of each aqueous solution (pH=7 is pure water) with pH values of 2, 4, 7, 9, and 10 is dropped onto the medical component at 25°C ± 2.0°C, and 1 second later, the contact angle of the droplet is 60° to 100°. From the viewpoint of suppressing changes in physical properties (contact angle) in response to pH changes, the medical component obtained using the medical resin composition of the present invention preferably has a standard deviation of the contact angle of the droplet over the entire pH range of 2.9 or less. From the same viewpoint, a smaller standard deviation is preferable, more preferably 2.0 or less, and particularly preferable 1.0 or less. Furthermore, from the viewpoint of suppressing changes in physical properties (contact angle) in response to pH changes in the acidic range (pH 2 to 7), the resin preferably contains one or more structures selected from those represented by formulas (1-1) and (1-4), and particularly preferably contains one or more structures selected from those represented by formulas (1-1) and (1-4c). Furthermore, from the viewpoint of suppressing changes in physical properties (contact angle) in response to pH changes in the basic range (pH 7 to 10), the resin preferably contains one or more structures selected from those represented by formulas (1-1) and (1-6), and particularly preferably contains one or more structures selected from those represented by formulas (1-1) and (1-6a).
[0056] Furthermore, the medical component obtained using the medical resin composition of the present invention exhibits improved antithrombotic properties. Specifically, a component made of a resin containing the atomic group represented by formula (1) at the ends of the side chains and / or main chain can be applied as an antithrombotic component. The antithrombotic component in the present invention is evaluated by a platelet adhesion test, and its superiority can be evaluated by a relative comparison with the platelet adhesion test of an antithrombotic reference component made of a reference resin. The procedure for the platelet adhesion test to evaluate antithrombotic activity is as follows: 1) Platelets are attached to both the antithrombotic component and the antithrombotic reference component. 2) The number of platelets attached to a predetermined area of the antithrombotic reference member is set to 100 as a relative value. 3) The number of platelets attached to a predetermined area of the antithrombotic member is considered to be 70 or less when compared to 2) above, indicating a superior antithrombotic member. This number is more preferably 50 or less, and even more preferably 20 or less. Detailed experimental procedures can be found in the examples described later. Furthermore, the antithrombotic reference member, i.e., the reference resin, was manufactured by the following procedure. <In the case of polysiloxane> The target is a resin containing the atomic group represented by formula (1) at the end of the side chain and / or main chain, wherein the side chain having the atomic group portion represented by formula (1) is a phenyl group or a hydrocarbon group. Further details can be found in Synthesis Example 3 and Comparative Synthesis Example 1 in the Examples. <For resins other than polysiloxane, such as epoxy resins, phenolic resins, novolac resins, polyimides, polyamides, polyesters, and polyethers> The objective is a resin that contains the atomic group represented by formula (1) as a hydrogen atom, based on the premise of a resin containing the atomic group represented by formula (1) at the end of the side chain and / or main chain. Details can be found in Example 8 and Comparative Example 4 of the Examples. Note that the reference resin may contain other side chains such as carboxylic acids, within a range that does not change the properties of the main chain from a synthesis standpoint.
[0057] From the viewpoint of improving antithrombotic properties as described above, component (A) of the medical resin composition of the present invention is preferably a resin containing one or more structures selected from those represented by formula (1-1), (1-3a), or formula (1-6a), and is particularly preferably a resin containing one or more structures selected from those represented by formula (1-1) or formula (1-6a). Since these resins have antithrombotic properties, they can be used as antithrombotic members.
[0058] The content of the atomic group represented by formula (1) in the resin may be 1% by mass or more and 95% by mass or less relative to the total amount of the resin, preferably 30% by mass or more and 90% by mass or less, and more preferably 50% by mass or more and 85% by mass or less. When the value is within the above range, the resin of the present invention has higher antithrombotic properties than the reference resin.
[0059] [Resin film] After applying the medical resin composition of the present invention onto a substrate, a resin film (hereinafter, those formed through curing or crosslinking by polymerization or condensation may be referred to as "cured films," and those formed through curing or crosslinking, and those formed without curing or crosslinking, may be collectively referred to as "resin films" or "coatings") can be formed on the substrate. The method of removing the solvent is not particularly limited, but it is desirable that the solvent be sufficiently removed by methods such as drying at room temperature, heating, or reduced pressure.
[0060] The substrate on which the resin film is formed is not particularly limited. Examples include polyethylene, polypropylene, polystyrene, polyvinyl chloride, nylon, polyurethane, polyurea, polylactic acid, polyglycolic acid, polyvinyl alcohol, polyvinyl acetate, poly(meth)acrylic acid, poly(meth)acrylic acid derivatives, polyacrylonitrile, poly(meth)acrylamide, poly(meth)acrylamide derivatives, polysulfone, polycarbonate, cellulose, cellulose derivatives, polysiloxane, glass, ceramic, and metal. These materials can be used individually or in combination of two or more. The substrate may be subjected to pretreatment such as surface cleaning with a solvent, UV ozone, plasma, or electron beam treatment as needed before forming the film obtained from the medical composition of the present invention.
[0061] The method for forming the resin film is not particularly limited, and known methods can be used. For example, methods such as coating using a brush, roller, or spin coater, spray coating, vapor deposition, or immersion can be used.
[0062] [Medical-grade resin molded products] The medical resin composition of the present invention can be used to obtain a molded article by removing the solvent and then molding it.
[0063] The method for obtaining the molded article is not particularly limited, but one example is to obtain the molded article by removing the solvent from the resin composition before molding, or by molding while removing the solvent. Furthermore, a molded article (cured product) may be obtained by curing or crosslinking. The method for obtaining the cured product is not particularly limited, but for example, one method is to obtain a molded cured product by removing the solvent from the resin composition and performing curing or crosslinking while molding. The curing method is not particularly limited, but if necessary, a crosslinking agent, a photopolymerization initiator, or a thermal polymerization initiator may be used in combination to promote curing or crosslinking. The method for removing the solvent is not particularly limited, but it is desirable that the solvent be sufficiently removed by methods such as drying at room temperature, heating, or reduced pressure.
[0064] The form of the molded product can be a molded body, a laminate, a cast product, or a film. Furthermore, the resulting cured product can be molded into shapes suitable for desired medical components, such as tubular, grooved, thread-like, or nonwoven fabric forms, including microchannels.
[0065] The molding method is not particularly limited, but generally known molding methods can be applied. Examples include injection molding, lamination molding, sheet molding, conventional spinning, and electrospinning. The resulting products can be molded into desired shapes such as tubular, grooved, thread-like, nonwoven fabric, porous, block, or lump forms. The obtained molded products can also be combined to obtain other molded products.
[0066] The method for producing the molded article is not particularly limited, but from the viewpoint of uniformity of the medical component, molding from a resin composition obtained by dissolving component (A) in component (B) is preferred.
[0067] Fluororesins used as medical components are generally poorly soluble in the solvent of component (B) above. While they may exhibit solubility only in special solvents, there was room for improvement in their versatility. On the other hand, the medical resin composition of the present invention has component (A) containing the HFIP group represented by formula (1) above, which is soluble in the highly versatile solvents that can be listed as component (B) above. From the viewpoint of the solubility of the resin in solvents, the resin composition of the present invention is useful as a medical resin composition. [Industrial applicability]
[0068] The present invention can provide a medical resin composition containing a hexafluoroisopropanol group. By containing a hexafluoroisopropanol group, a medical resin composition is provided that has an appropriate water droplet contact angle while avoiding excessively high water repellency. Accordingly, the medical resin composition of the present invention is suitable for providing a medical resin composition, medical component, and method for molding a medical component that is suitable for controlling cell adhesion, biocompatibility, antithrombotic properties, and suppressing biofouling. Specific examples of medical components include pharmaceuticals, quasi-drugs, drug delivery system materials, pH adjusters, molding aids, microfluidics, test kits, cell scaffold materials, packaging materials, artificial blood vessels, hemodialysis membranes, catheters, blood filters, blood storage packs, and artificial organs. [Examples]
[0069] Embodiments of the present invention will be specifically described based on examples, comparative examples, and reference examples, but the present invention is not limited to these embodiments.
[0070] The physical properties of the polymers synthesized in the following synthesis examples were evaluated using the method described below.
[0071] [Measurement of polymer molecular weight distribution] The weight-average molecular weight (Mw) and molecular weight dispersion (ratio of number-average molecular weight Mn to weight-average molecular weight Mw; Mw / Mn) of polymers were measured using gel permeation chromatography (hereinafter sometimes referred to as GPC) under the following conditions, with polystyrene used as the standard substance to create a calibration curve and calculate the measured values. Equipment: Manufactured by Tosoh Corporation, Product name: HLC-8320GPC Column: Manufactured by Tosoh Corporation, Product name: TSK gel GMH XL Connect three of them in series. Eluent: Tetrahydrofuran (sometimes referred to as THF)
[0072] 4-hydroxy-α,α-bis(trifluoromethyl)benzenemethanol, used as a raw material in the synthesis example described below, can be synthesized by referring to previously reported information (JP 2012-201608). Furthermore, 3,3'-bis(1-hydroxy-1-trifluoromethyl-2,2,2-trifluoroethyl)-4,4'-methylenedianiline (hereinafter sometimes referred to as HFA-MDA), used as a raw material in the synthesis example described below, can be synthesized by referring to previously reported information (JP 2019-199459). Additionally, 3-(triethoxysilyl)-α,α-bis(trifluoromethyl)benzenemethanol (hereinafter sometimes referred to as HFA-Si), used as a raw material in the synthesis example described below, can be synthesized by referring to previously reported information (WO2019 / 167770), however, the synthesis methods for these compounds are not particularly limited.
[0073] [Monomer synthesis] (Synthesis Example 1) Synthesis of Monomer M-1 30.5 g, 168 mmol of 1,1,1-trifluoro-2-(trifluoromethyl)-4-penten-2-ol and 23.7 g, 201.7 mmol of methyldiethoxysilane were placed in a 100 mL three-necked flask, and the mixture was heated to an internal temperature of 80°C while stirring. After adding Karsted catalyst (2% Pt xylene solution, Aldrich), the mixture was stirred for 7 hours. Subsequently, the reaction mixture was purified by distillation at a distillation temperature of 100°C and a reduced pressure of 1.0 kPa to obtain 42.7 g of 5-(diethoxymethylsilyl)-1,1,1-trifluoro-2-trifluoromethyl-2-pentanol (monomer M-1) in a yield of 67.4%. [ka]
[0074] (Synthesis Example 2) Synthesis of Monomer M-2 30.0 g (115 mmol) of 4-hydroxy-α,α-bis(trifluoromethyl)benzenemethanol was placed in a 500 mL four-necked flask. Next, 230 mL of tetrahydrofuran (hereinafter sometimes referred to as THF) and 15.2 g (149.5 mmol, 1.3 eq.) of triethylamine were added to the nitrogen-purged flask, and the flask was cooled with ice to bring the internal temperature to below 5°C. Using a dropping funnel, 13.3 g (126.5 mol, 1.1 eq.) of methacryloyl chloride was added dropwise over 1 hour, and the mixture was stirred at room temperature for 2 hours. Then, 150 mL of 10% hydrochloric acid aqueous solution was added and stirred, and the aqueous layer was removed by transferring to a separatory funnel. The organic layer was washed with saturated sodium chloride aqueous solution, and THF was removed by vacuum distillation using an evaporator. Purification by recrystallization using heptane and toluene yielded 33.0 g of 2-methyl-2-propenoic acid-4-[2,2,2-trifluoro-1-hydroxy-1-(trifluoromethyl)ethyl]phenyl ester (monomer M-2) in a yield of 87.0%. [ka]
[0075] [Polymer synthesis] (Synthesis Example 3) Synthesis of Polymer P-1 In a 100 mL three-necked flask, monomer M-1 (10.0 g, 29.2 mmol) and trimethoxymethylsilane (5.2 g, 29.2 mmol) were added, and aqueous acetic acid (4.4 mg acetic acid, 0.07 mmol; 6.6 g water, 365 mmol) was added while stirring. The mixture was then stirred at 75°C for 7 hours to carry out hydrolysis and condensation reactions. After the reaction was complete, the reaction solution was allowed to return to room temperature, washed three times with distilled water, and then concentrated under reduced pressure using an evaporator to obtain polymer (P-1) as a viscous liquid (7.0 g). The GPC weight-average molecular weight (Mw) was 2,310, and the molecular weight dispersion (Mw / Mn) was 1.1.
[0076] (Synthesis Example 4) Synthesis of Polymer P-2 In a nitrogen-purged flask, 14.5 g (30.5 mmol) of monomer (M-2), 33.9 g of methyl ethyl ketone (monomer concentration 30% by mass), and 0.4 g (1.6 mmol, 5 mol%) of 2,2'-azobis(isobutyrate)dimethyl were added as a polymerization initiator. The mixture was stirred at 80°C for 4 hours to carry out the polymerization reaction. After the reaction was complete, the reaction product was purified by reprecipitation with 150 g of heptane, and the resulting solid was recovered by filtration. Subsequently, the obtained solid was dried under reduced pressure to obtain 14.0 g of polymer (P-2) as a white solid in 97% yield. The GPC weight-average molecular weight (Mw) was 50,870, and the molecular weight dispersion (Mw / Mn) was 2.6. [ka]
[0077] (Synthesis Example 5) Synthesis of Polymer P-3 In a 500 mL four-necked flask equipped with a nitrogen inlet tube and stirring blades, 134 g of dimethylacetamide was added, and 21.2 g (40 mmol) of HFA-MDA was stirred and dissolved. Then, 12.4 g (40 mmol) of 4,4'-oxydiphthalic acid dianhydride was added, and the mixture was stirred at room temperature (20°C) for 3 hours to obtain a polyamic acid solution (polymer P-3). The weight-average molecular weight (Mw) of the polyamic acid was 24,700, and the molecular weight dispersion (Mw / Mn) was 6.0. [ka] [ka]
[0078] (Synthesis Example 6) Synthesis of Polymer P-4 In a 500 mL four-necked flask equipped with a nitrogen inlet tube and stirring blades, 132 g of N-methyl-2-pyrrolidone was added, and 21.2 g (40 mmol) of HFA-MDA was stirred and dissolved. Subsequently, 6.6 g (84 mmol) of pyridine was added, and after cooling to an internal temperature of 10°C, 11.8 g (40 mmol) of 4,4'-oxybis(benzoyl chloride) was added and stirred for 20 minutes, then stirred at room temperature (20°C) for 2 hours. After the reaction was complete, the obtained solution was added to 1 L of 10% methanol aqueous solution, and the precipitated solid was collected by filtration. Subsequently, it was dried under reduced pressure to obtain polyamide (polymer P-4). The weight-average molecular weight (Mw) of the polyamide was 25,700, and the molecular weight dispersion (Mw / Mn) was 4.3. [ka]
[0079] (Synthesis Example 7) Synthesis of Polymer P-8 50.0 g of HFA-Si (158 mmol) was placed in a 300 mL three-necked flask, and aqueous acetic acid (474 mg of acetic acid, 7.90 mmol of water, 8.97 g of water, 498 mmol of water) was added while stirring. The mixture was then stirred at 75°C for 24 hours to carry out hydrolysis and condensation reactions. After the reaction was complete, the reaction solution was allowed to return to room temperature, 50.0 g of diisopropyl ether was added, and then the mixture was washed twice with distilled water. Subsequently, 2-methoxy-1-methylethyl acetate was added to bring the polymer concentration to 50% by mass, and the solution of polymer P-8 was obtained by concentrating under reduced pressure using an evaporator. The weight-average molecular weight (Mw) of the GPC was 1,760, and the molecular weight dispersion (Mw / Mn) was 1.1. [ka]
[0080] (Comparative Synthesis Example 1) In Synthesis Example 3, the procedure was carried out in the same manner as in Synthesis Example 3, except that monomer M-1 was changed to dimethyldiethoxysilane, and polymer (P-5) was obtained as a colorless, transparent viscous liquid (14.0 g). The GPC weight-average molecular weight (Mw) was 1,300, and the molecular weight dispersion (Mw / Mn) was 1.3.
[0081] (Comparative Synthesis Example 2) In Synthesis Example 4, the procedure was carried out in the same manner as in Synthesis Example 4, except that monomer M-2 was replaced with phenyl methacrylate, and polymer P-6 was obtained as a white solid (14.0 g). The yield of the obtained polymer was 97%, the GPC weight-average molecular weight (Mw) was 16,270, and the molecular weight dispersion (Mw / Mn) was 3.0. [ka]
[0082] (Comparative Synthesis Example 3) In Synthesis Example 5, the procedure was carried out in the same manner as in Synthesis Example 5, except that HFA-MDA was replaced with 4,4'-methylenedianiline, to obtain polymer P-7 (polyamic acid solution). The weight-average molecular weight (Mw) of polymer P-7 was 25,100, and the molecular weight dispersion (Mw / Mn) was 5.6. [ka]
[0083] (Comparative Synthesis Example 4) In Synthesis Example 7, the procedure was the same as in Synthesis Example 7, except that HFA-Si was replaced with phenyltriethoxysilane, to obtain a solution of polymer P-9. The weight-average molecular weight (Mw) of polymer P-9 was 980, and the molecular weight dispersion (Mw / Mn) was 1.2. [ka]
[0084] [Contact angle measurement] On the horizontal surface of each polymer film formed on a glass substrate, 2 μL of ion-exchanged water was placed with a syringe under the condition of room temperature (25 °C ± 2.0 °C), and the contact angle of the droplet 1 second after placing the droplet was measured using a contact angle meter (Kyowa Interface Science Co., Ltd., model DMs-601). <Evaluation of pH dependence> The dropped aqueous solution used the pH standard solution set: oxalate standard solution (pH = 2), phthalate standard solution (pH = 4), phosphate standard solution (pH = 7), borate standard solution (pH = 9), carbonate standard solution (pH = 10) (all manufactured by Horiba Advanced Technology Co., Ltd.) to evaluate the pH dependence of the contact angle.
[0085] (Example 1) The polymer P-1 obtained in Synthesis Example 3 was adjusted to a 20% by mass butyl acetate solution, and the solution was spin-coated (1000 rpm for 1 minute) on a glass substrate and then heat-treated at 180 °C for 2 hours to obtain a polysiloxane cured film having a film thickness of 1 to 2 μm.
[0086] (Example 2) The polymer P-2 obtained in Synthesis Example 4 was adjusted to a 10% by mass butyl acetate solution, and the solution was spin-coated (1000 rpm for 1 minute) on a glass substrate and then heat-treated at 120 °C for 10 minutes to obtain a film having a film thickness of 1 to 2 μm.
[0087] (Example 3) The polymer P-3 solution obtained in Synthesis Example 5 was spread on a glass substrate, and after reaching a rotational speed of 600 rpm in 10 seconds with a spin coater, it was held for 60 seconds to form a film of uniform thickness on the glass substrate. This film was heated at 250 °C for 2 hours in a nitrogen atmosphere. Then, it was cooled to room temperature to obtain a polyimide film (film thickness 2.4 μm).
[0088] (Example 4) The operation was carried out in the same procedure as in Example 3 except that the heating conditions in Example 3 were changed to 300 °C for 2 hours to produce a polyimide film (film thickness 1.6 μm).
[0089] (Example 5) The polymer P-4 obtained in Synthesis Example 6 was dissolved in γ-butyrolactone (solid content concentration 20% by mass). The solution was then spread onto a glass substrate and a uniform thickness film was formed on the glass substrate by spin-coating it to a rotation speed of 800 rpm in 10 seconds and holding it for 60 seconds. This film was heated at 150°C for 2 hours under a nitrogen atmosphere. After that, it was cooled to room temperature to obtain a polyamide film (thickness 2.2 μm). Solid content concentration refers to the concentration of components other than the volatile solvent in the solution.
[0090] (Example 6) Except for changing the heating conditions to 250°C, the procedure was the same as in Example 5 to obtain a polyamide film (thickness 1.3 μm).
[0091] (Example 9) The polymer P-8 solution obtained in Synthesis Example 7 was spread onto a glass substrate, and a film of uniform thickness was formed on the glass substrate by spin-coating it to a rotation speed of 1000 rpm in 10 seconds and then holding it for 30 seconds. This film was heated at 100°C for 1 minute, and then at 130°C for 1 hour. After that, it was cooled to room temperature to obtain a polysiloxane-cured film (film thickness 4.2 μm).
[0092] (Comparative Example 1) In Example 1, the procedure was carried out in the same manner as in Example 1, except that polymer P-1 was replaced with polymer (P-5), to obtain a polysiloxane cured film having a thickness of 1 to 2 μm.
[0093] (Comparative Example 2) In Example 2, the procedure was carried out in the same manner as in Example 2, except that polymer P-2 was replaced with polymer (P-6), to obtain a polymethacrylate coating with a thickness of 1 to 2 μm.
[0094] (Comparative Example 5) In Example 9, the procedure was carried out in the same manner as in Example 9, except that polymer P-8 was replaced with polymer (P-9), to obtain a polysiloxane cured film with a thickness of 0.56 μm.
[0095] (Reference example 1) Sheets made from Silpot 184 (Dow, PDMS elastomer) were washed with water and then dried under reduced pressure at room temperature for 3 hours to obtain sheets (1 mm thick). In Table 1, these are labeled as PDMS.
[0096] The contact angle of water droplets of the cured film with a thickness of 1 to 5 μm obtained above was measured using a contact angle meter. The results are shown in Table 1. [Table 1]
[0097] Comparing the cured film of Example 1 (derived from P-1), in which the polymer main chain is a siloxane skeleton, with the cured film of Comparative Example 1 (derived from P-5), Example 1, which contains the atomic group represented by formula (1), is able to avoid excessively high water repellency and utilize the low intermolecular cohesive force due to the small surface free energy based on the fluorine of the atomic group. Furthermore, comparing the cured film of Example 9 (derived from P-8), in which the polymer main chain has a siloxane skeleton and aromatic rings in the side chains, with the cured film of Comparative Example 5 (derived from P-9), Example 9, which contains the atomic group represented by formula (1), is able to avoid excessively high water repellency and utilize the low intermolecular cohesive force due to the small surface free energy based on the fluorine of the atomic group. Furthermore, comparing the coating of Example 2 (derived from P-2), in which the polymer main chain is an ethylene skeleton, with the coating of Comparative Example 2 (derived from P-6), Example 2, which contains the atomic group represented by formula (1), is able to avoid excessively high water repellency and utilize the low intermolecular cohesive force due to the small surface free energy based on the fluorine of the atomic group. Thus, when comparing the main chains of the polymers with the same (or similar) structure, it was found that the films according to the examples containing the atomic group represented by the above formula (1) each showed a lower contact angle than the films according to the corresponding comparative examples. Incidentally, the above tendency was confirmed in a wide pH range (pH = 2 to 10). Also, the films according to the examples had significantly lower values than the contact angle of PDMS shown in the reference example. Also, the films according to the polymers of Examples 3 to 6 also showed contact angles equivalent to those of the films according to the polymers of Examples 1, 2, and 9. That is, it is suggested that these films are imparted with hydrophilicity by the HFIP group. From this result, it can be seen that these polymers are polymers having an appropriate water droplet contact angle while avoiding excessive water repellency.
[0098] As shown in Table 1, it was found that for the films according to the polymers of Examples 1 to 6 and 9, the standard deviation of the contact angle was 2.9 or less in the contact angles with aqueous solutions having pH values of 2, 4, 7, 9, and 10 (pH = 7 is pure water). Among the examples, the films made of the polymers of Examples 1, 4, 6, or 9 suggest that they have good alkali resistance because the above standard deviation at pH 7 to 10 is smaller.
[0099] (Example 7) The platelet adhesion test of the polysiloxane cured film obtained in Example 1 was carried out as follows. Bovine preserved blood (manufactured by ROCKLAND) was centrifuged at 2400 rpm for 7 minutes, and the supernatant plasma was collected. The obtained plasma was centrifuged again at 3000 rpm for 10 minutes, and platelet-rich plasma (PRP) was collected from the sedimentation part. The obtained PRP was diluted 50 times with phosphate buffered saline to prepare a platelet solution with a platelet concentration of 4.7×10 7 cell / mL. 400 μL of the obtained platelet solution was dropped onto the polysiloxane cured film obtained in Example 1 and left standing at 37°C for 1 hour. Then, it was washed 3 times with phosphate buffered saline and immersed in a 1% aqueous glutaraldehyde solution at 37°C for 2 hours to fix the tissue. Then, after washing with ion-exchanged water, it was air-dried. The obtained sample was observed by SEM in a predetermined area (4600 μm2 The number of platelets in the area was measured. Measurements were taken at four locations in the area, and the total number of platelets was calculated. Note that a lower number of platelets observed by SEM indicates superior antithrombotic properties. The platelet count in Example 7 is shown in Table 2 as a relative value with the platelet count in Comparative Example 3 (described later) set to 100.
[0100] (Comparative Example 3) The polysiloxane cured film obtained in Comparative Example 1 was subjected to the same platelet adhesion test as in Example 7. The results are shown in Table 2.
[0101] (Example 8) The polymer P-3 solution obtained in Synthesis Example 5 was spread onto a glass substrate, and a uniform thickness film was formed on the glass substrate by spin-coating it to a rotation speed of 600 rpm in 10 seconds and then holding it for 60 seconds. This film was heated in a nitrogen atmosphere at a temperature of 280°C for 2 hours. After that, it was cooled to room temperature to obtain a polyimide film (thickness 2.2 μm). A platelet adhesion test similar to that in Example 7 was performed on the obtained polyimide film. The platelet count in Example 8 is shown in Table 3 as a relative value with the platelet count in Comparative Example 4 (described later) set to 100.
[0102] (Comparative Example 4) In Example 8, the procedure was carried out in the same manner as in Example 8, except that polymer P-3 was changed to polymer P-7, to obtain a polyimide film (thickness 2.5 μm). The resulting polyimide film was subjected to the same platelet adhesion test as in Example 7. The results are shown in Table 3.
[0103] (Example 10) The polymer P-8 solution obtained in Synthesis Example 7 was spread onto a glass substrate, and this film was heated at 100°C for 1 minute, then at 130°C for 1 hour. After that, it was cooled to room temperature to obtain a polysiloxane film (thickness 188 μm). The obtained polysiloxane film was subjected to the same platelet adhesion test as in Example 7. The platelet count in Example 10 is shown in Table 4 as a relative value with the platelet count in Comparative Example 6 (described later) set to 100.
[0104] (Comparative Example 6) In Example 10, the procedure was carried out in the same manner as in Example 10, except that polymer P-8 was changed to polymer P-9, to obtain a polysiloxane film (thickness 54 μm). The resulting polysiloxane film was subjected to the same platelet adhesion test as in Example 10. The results are shown in Table 4.
[0105] [Table 2]
[0106] [Table 3]
[0107] [Table 4] The polyimide film of Example 8 (relative platelet count of 60) was found to have fewer attached platelets compared to the polyimide film of Comparative Example 4, which did not contain HFIP groups. Similarly, the polysiloxane film of Example 10 (relative platelet count of 42) was found to have fewer attached platelets compared to the polysiloxane film of Comparative Example 6, which did not contain HFIP groups. Furthermore, the polysiloxane cured film of Example 1 (relative platelet count of 10) was found to have significantly fewer attached platelets compared to the polysiloxane cured film of Comparative Example 1, which did not contain HFIP groups. The results described above show that the medical resin composition of the present invention exhibits excellent antithrombotic properties.
[0108] Based on these results, the medical resin composition of the present invention is expected to be applicable to medical compositions.
Claims
1. A medical resin composition comprising the following component (A) and component (B): (A): A resin containing an atomic group represented by the following formula (1): (B): Solvent 【Chemistry 1】 (In the above formula (1), the wavy lines represent bonds to other atomic groups.)
2. 2. The medical resin composition according to claim 1, wherein the component (A) is at least one selected from the group consisting of epoxy resins, phenolic resins, novolac resins, polysiloxanes, polyimides, polyamides, polyesters, and polyethers.
3. The medical resin composition according to claim 1 or 2, characterized in that the component (A) contains one or more selected from the group consisting of structures represented by the following formulas (1-1) to (1-6): 【Chemistry 2】 (In the above formula (1-1), the wavy lines represent bonds to other atomic groups.) 【Chemistry 3】 (In the above formula (1-2), the wavy lines represent bonds to other atomic groups.) 【Chemistry 4】 In the formula (1-3), Ar1 is a group containing an aromatic hydrocarbon group having 6 to 24 carbon atoms, and some or all of the hydrogen atoms of the aromatic hydrocarbon group may be substituted with an alkyl group having 1 to 3 carbon atoms; 2 -, -CO-, -SO 2 -, -C(CH 3 ) 2 -, -C(CF 3 ) 2 -, ma represents an integer of 1 to 3, and na represents an integer of 1 to 4. In the formula (1-3), the wavy line represents a bond to another atomic group. 【Chemistry 5】 In the formula (1-4), Ar2 is a group containing an aromatic hydrocarbon group having 6 to 24 carbon atoms, and some or all of the hydrogen atoms of the aromatic hydrocarbon group may be substituted with an alkyl group having 1 to 3 carbon atoms, and —CH 2 -, -CO-, -SO 2 -, -C(CH 3 ) 2 -, -C(CF 3 ) 2 -, mb represents an integer of 1 to 3, and nb represents an integer of 1 to 4. In the formula (1-4), the wavy line represents a bond to another atomic group. 【Chemistry 6】 (In the above formula (1-5), R 1 is a hydrogen atom or an alkyl group having 1 to 4 carbon atoms; R 2 is a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or a group containing an aromatic hydrocarbon having 6 to 24 carbon atoms; R 3 is an alkyl group having 1 to 4 carbon atoms, t is an integer of 1 or 2, p is an integer of 0 to 2, nc is an integer of 1 to 3, and the wavy line represents a bond to another atomic group. 【Chemistry 7】 In the formula (1-6), Ar3 is a group containing an aromatic hydrocarbon group having 6 to 24 carbon atoms, and some or all of the hydrogen atoms of the aromatic hydrocarbon group may be substituted with an alkyl group having 1 to 3 carbon atoms; 2 -, -CO-, -SO 2 -, -C(CH 3 ) 2 -, -C(CF 3 ) 2 -, md represents an integer of 1 to 3, and nd represents an integer of 1 to 4. In the formula (1-6), the wavy line represents a bond to another atomic group.
4. The medical resin composition according to claim 3, wherein in the formula (1-3), the aromatic hydrocarbon group having 6 to 24 carbon atoms contained in Ar1 is a group containing a benzene ring, a naphthalene ring, or an anthracene ring.
5. The medical resin composition according to claim 3, wherein in the formula (1-4), the aromatic hydrocarbon group having 6 to 24 carbon atoms contained in Ar2 is a group containing a benzene ring, a naphthalene ring, or an anthracene ring.
6. The medical resin composition according to claim 3, wherein in the formula (1-6), the aromatic hydrocarbon group having 6 to 24 carbon atoms contained in Ar3 is a group containing a benzene ring, a naphthalene ring, or an anthracene ring.
7. The medical resin composition according to claim 3 or 4, characterized in that the structure represented by the formula (1-3) is one or more selected from the group consisting of structures represented by the following formulas (1-3a) to (1-3f): 【Chemistry 8】 (In the above formula (1-3a), the wavy lines represent bonds to other atomic groups.) 【Chemistry 9】 (In the above formula (1-3b), the wavy lines represent bonds to other atomic groups.) 【Chemistry 10】 (In the above formula (1-3c), the wavy lines represent bonds to other atomic groups.) 【Chemistry 11】 (In the above formula (1-3d), the wavy lines represent bonds to other atomic groups.) 【Chemistry 12】 (In the above formula (1-3e), the wavy lines represent bonds to other atomic groups.) 【Chemistry 13】 (In the above formula (1-3f), the wavy lines represent bonds to other atomic groups.)
8. The medical resin composition according to claim 3 or 5, characterized in that the structure represented by the formula (1-4) is one or more selected from the group consisting of structures represented by the following formulas (1-4a) to (1-4c): 【Chemistry 14】 (In the above formula (1-4a), the wavy lines represent bonds to other atomic groups.) 【Chemistry 15】 (In the above formula (1-4b), the wavy lines represent bonds to other atomic groups.) 【Chemistry 16】 (In the formula (1-4c), n represents an integer of 1 to 3, and the wavy line represents a bond to another atomic group.)
9. The medical resin composition according to claim 3 or 6, wherein the structure represented by the formula (1-6) is a structure represented by the following formula (1-6a): 【Chemistry 17】 (In the above formula (1-6a), the wavy lines represent bonds to other atomic groups.)
10. The component (B) is The medical resin composition according to any one of claims 1 to 9, characterized in that the solvent is at least one selected from the group consisting of water, methanol, ethanol, isopropanol, 1,1,1-trifluoroethanol, 1,1,1,3,3,3-hexafluoroisopropanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, diethyl ether, diisopropyl ether, tetrahydrofuran, benzene, toluene, xylene, hexane, heptane, octane, cyclohexane, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, cyclohexanone, ethyl lactate, butyl acetate, γ-butyrolactone, diacetone alcohol, diglyme, methyl isobutyl ketone, 3-methoxybutyl acetate, 2-heptanone, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.
11. The medical resin composition according to any one of claims 1 to 10, wherein the component (A) further contains a polymerizable site.
12. Further comprising a third component, the third component is at least one selected from the group consisting of polyethylene, polypropylene, polyvinyl chloride, nylon, polyurethane, polylactic acid, polyglycolic acid, poly(meth)acrylic acid, poly(meth)acrylic acid derivatives, poly(meth)acrylamide, poly(meth)acrylamide derivatives, polysulfone, cellulose, cellulose derivatives, silicone, and polydimethylsiloxane; The medical resin composition according to any one of claims 1 to 11.
13. The medical resin composition according to any one of claims 1 to 12, further comprising a crosslinking agent.
14. A medical component obtained by curing the medical resin composition according to any one of claims 11 to 13.
15. A method for curing the medical resin composition according to any one of claims 11 to 13.
16. A medical component obtained by molding the medical resin composition according to any one of claims 1 to 13.
17. 17. The medical device according to claim 14 or 16, wherein 2 μL of aqueous solutions having pH values of 2, 4, 7, 9, and 10 (pH=7 is pure water) are dropped at 25° C.±2.0° C., and the contact angles of the droplets are measured after 1 second, and the standard deviation of the contact angles is 2.9 or less.
18. A method for molding the medical resin composition according to any one of claims 1 to 13.
19. An antithrombotic member made of a resin, The resin has a main chain and a side chain, An antithrombotic material, wherein the side chain and / or an end of the main chain contain an atomic group represented by the following formula (1), and the platelet adhesion number is 70 or less as a result of a platelet adhesion test performed according to the following procedures 1), 2), and 3). 【Chemistry 18】 1) Platelets are allowed to adhere to both the antithrombogenic member and the antithrombogenic reference member made of a reference resin. 2) The number of platelets adhering to a specific area of the antithrombotic reference member is set to 100 as a relative value. 3) The number of platelets adhering to a predetermined area of the antithrombotic material is compared with that of 2) above. Here, the reference resin is defined as follows. When the antithrombotic member is made of polysiloxane: The present invention provides a resin that contains a side chain having an atomic group moiety represented by formula (1) as a phenyl group or a hydrocarbon group, the side chain having the atomic group represented by formula (1) being a target resin that contains the atomic group represented by formula (1) at the end of a side chain and / or a main chain. When the antithrombotic component is made of a resin other than polysiloxane: The present invention provides a resin that contains the atomic group represented by the formula (1) as a hydrogen atom, on the premise that the resin contains the atomic group represented by the formula (1) at the end of the side chain and / or the main chain.